Shaping Minds Through Art: A Systematic Review of Aesthetic and Cognitive Interactions - Sangvanich, Khanobbhorn; Phetmalaikul, Theeraphab (Journal of Urban Culture Research, 2024)
This study explores the implication and application of art education to enhance cognition through aesthetic development via a systematic literature review. Articles published from 2018 to 2023 were gathered from Scopus, Academic Search Ultimate, JSTOR, ScienceDirect, and SpringerLink. Initial keywords inquiries, “aesthetic” and “cognition” were 2,553 articles. After applying inclusion and exclusion criteria, 12 articles remained for review. Findings indicate aesthetic is a form of cognition, that combines emotions and senses. Aesthetic and cognition can arise and develop at any age. A person’s level of personal aesthetic development increases with age and experience, varying among individuals. Some research found that various factors such as age, experience, environment, and art education promote the experiential interplay between aesthetic and cognition, this means developers could use experiential programs to increase aesthetic. Aesthetic development benefits society, individual’s health, and well-being. Moreover, aesthetic experience involves sensory, motor, emotional, and memory faculties.